Droplet digital PCR assay for precise determination of FRS2 gene copy number in bladder cancer - Jinqian Li; Jiaqi Liang; Yinyan Xu; Wei Tan; Guanzheng Chen; Tong Ou (BMC Cancer)
Abstract Objective To establish and validate a droplet digital PCR (ddPCR) assay for quantifying FRS2 gene copy number in formalin-fixed paraffin-embedded (FFPE) bladder cancer tissue samples, and to evaluate its analytical performance. Methods The ddPCR assay was developed using FRS2 as the target gene and RPP30 as the reference gene. Artificial plasmids, genomic DNA from urinary sediment of healthy individuals and cell lines were used as templates to assess the assay’s precision, minimum reliable input DNA, and linearity. Fluorescence in situ hybridization (FISH) was employed to validate the accuracy of the ddPCR results. Results One-dimensional fluorescence amplitude plots showed clear separation between positive and negative droplets for both FRS2 and RPP30. Duplex detection of FRS2 and RPP30 within the same reaction showed no interference between primers or probes. The assay exhibited excellent repeatability and precision, with intra-assay coefficient of variation (CV)% of 2.58% and 3.75%, and inter-assay CV% of 2.68% and 3.79%, across 20 ng and 2 ng input levels, respectively. The minimum reliable input DNA amount was determined to be 2 ng, and a strong linear relationship was observed (R2 >0.99). Compared to FISH, the ddPCR assay showed 100% sensitivity, 100% specificity, and a kappa value of 1. Conclusion The developed ddPCR assay enables accurate and reliable quantification of FRS2 copy number in FFPE samples, offering a promising tool for auxiliary diagnosis and prognostic assessment in bladder cancer.